Identifikasi dan Potensi Probiotik Bakteri Asam Laktat pada Pangan Fermentasi Lokal - Zaenab Fauziyah; Lista Nia; Febbi Julia Nandi; Rahmad Lingga; Henny Helmi (JURNAL BIOS LOGOS, 2023)
Lactic Acid Bacteria (LAB) are bacteria involved in food fermentation processes and can be used as probiotics. This study aims to isolate, identify and determine the probiotic potential of Lactic Acid Bacteria (LAB) at the end of the fermentation of local food on the island of Bangka and South Sumatra (aruk rice, anchovy sauce and tempoyak). Isolation and identification of lactic acid bacteria were carried out macroscopically, microscopically, biochemically and molecularly assays based on 16S rRNA. The probiotic potency of the isolates was tested based on their resistance to acid and antibacterial activity. LAB that plays a role in the process of making aruk rice is Lactobacillus plantarum with rod-shaped characteristics, gram positive, does not have the catalase enzyme, is able to ferment glucose into acid, is able to ferment lactose and sucrose, does not move, is resistant to acids and has antibacterial activity against Staphylococcus aureus.